2018
DOI: 10.1007/s10295-017-1990-4
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Escherichia coli for efficient coproduction of polyhydroxyalkanoates and 5-aminolevulinic acid

Abstract: Single-cell biorefineries are an interesting strategy for using different components of feedstock to produce multiple high-value biochemicals. In this study, a strategy was applied to refine glucose and fatty acid to produce 5-aminolevulinic acid (ALA) and polyhydroxyalkanoates (PHAs). To express the ALA and PHAs dual-production system efficiently and stably, multiple copies of the poly-β-3-hydroxybutyrate (PHB) synthesis operon were integrated into the chromosome of Escherichia coli DH5αΔpoxB. The above strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
0
7
0
3
Order By: Relevance
“…The parent strain BW24 produced 5.3 g/L ALA and the highest OD 600 reached 30.5 (Figure b,c). In previous studies, acetate accumulation was observed for the ALA‐producing E. coli strain (X. Zhang et al, ). In our case, acetate was also the main by‐product, which was accumulated at 6.1 g/L at the end of fermentation (Figure d).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The parent strain BW24 produced 5.3 g/L ALA and the highest OD 600 reached 30.5 (Figure b,c). In previous studies, acetate accumulation was observed for the ALA‐producing E. coli strain (X. Zhang et al, ). In our case, acetate was also the main by‐product, which was accumulated at 6.1 g/L at the end of fermentation (Figure d).…”
Section: Resultsmentioning
confidence: 82%
“…Cell integrity was monitored by double staining of cells by fluorescent probes fluorescein diacetate (FDA) and propidium iodide (PI) as described previously (M. Zhang et al, ). Bacterial cells with intact membranes will exclude PI but be stained by FDA and emit green fluorescence.…”
Section: Methodsmentioning
confidence: 99%
“…To explore the feasibility of T4 DNA ligase-mediated microbial mutagenesis, the polyhydroxybutyrate (PHB) producing E. coli XLPHB, which harbors chromosomal integrated PHB biosynthesis genes phbCAB from Ralstonia eutropha , was subjected to mutagenesis and screening with T4 DNA ligase expressed in vivo [12] . Generally, there was nearly no colony on the plate after the cells were treated by ARTP for 60-s (Additional file 1: Fig.…”
Section: Resultsmentioning
confidence: 99%
“…E. coli DH5α strain was used for molecular cloning and plasmids propagation. Engineered PHB producing E. coli XLPHB strain was subjected to ARTP treatment [12, 31].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation